Green finance investment and climate change mitigation in OECD-15 European countries: RALS and QARDL evidence - Ali, Mumtaz; Seraj, Mehdi; Turuc, Fatma; Tursoy, Turgut; Uktamov, Khusniddin Fakhriddinovich (Springer, 2024)
Green finance is an organized financial activity meant to improve the environment. Regardless of its critical role in mitigating climate change, green finance faces a significant investment shortfall. Green financing is a feasible way to close the gap in green investment. Despite the potential benefits of green finance in green renewable energy technologies, this study topic has received little attention. Investment in green energy projects draws attention since it eliminates the negative consequences of fossil fuels while also conserving the environment. This research looks into the nexus between investments in green finance, renewable energy consumption, carbon dioxide, foreign direct investment, remittances, inflation, gross fixed capital formation, trade openness, and human capital for the OECD-15 European countries, utilizing newly developed Residual Augmented Least Squire (RALS) cointegration technique and the QARDL model for the period spanning from 1990 to 2020. In empirical results, the RALS cointegration test confirms the cointegration link between the studied antecedents. Additionally, Quantile Autoregressive Distributed Lag Mondel (QARDL) empirical estimates show that the lag of renewable energy consumption, foreign direct investment, gross capital creation, trade openness, and human capital all have substantial influence on green finance investment. Carbon dioxide emissions and inflation, on the other hand, are proven to be adversely related. However, remittances have a negligible relationship with green finance investment. The results of this research provide insightful information on the state of green finance investments now and their requirements in the future. These insights will be beneficial for researchers, policymakers, and practitioners as they work towards enhancing and advocating for the implementation of green finance investment initiatives and endeavors aimed at mitigating climate change.
Keywords: Climate change; Green finance investment; Renewable energy; Foreign direct investment RALS and QARDL; OECD-15 European countries